Determinants of Tax Avoidance in Basic and Chemical Industry Companies: Political Connections in Share Ownership as a Control Variable - Kurnia Heriansyah; Lazarus Sinaga; Cotoro Mukri; Hanna Aulia (Jurnal Price : Ekonomi dan Akuntasi, 2026)
This study examines the effects of financial structure, profitability, firm size, and corporate social responsibility (CSR) on tax avoidance, with political connections in share ownership serving as a control variable. The study focuses on companies in the Basic and Chemical Industry listed on the Main Board of the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative research approach was employed using secondary data obtained from annual reports and audited financial statements. The study applied a saturated sampling technique, resulting in 35 firm-year observations from seven companies. Panel data regression analysis was performed using EViews 13, with the Fixed Effect Model (FEM) selected based on the Chow and Hausman tests. The findings indicate that financial structure and corporate social responsibility have a significant positive effect on tax avoidance, suggesting that debt financing and CSR expenditures contribute to corporate tax planning through legally permitted tax deductions. In contrast, profitability and firm size do not significantly affect tax avoidance. The regression model explains 55.27% of the variation in tax avoidance, indicating satisfactory explanatory power. These findings contribute to the literature on corporate taxation by providing empirical evidence from politically connected firms operating in Indonesia's basic and chemical industry and offer practical implications for policymakers in strengthening corporate tax governance.